A Cross-Sectional Study on the Nutritional Status of the Elderly in Limau Manis Subdistrict, Padang - Fitratur Rahmah Agustina; Aprilya Roza Werdani; Afifah Amatullah; Gandari Despita Putri; Bunga Oktria; Rahayu Rika Destia; Dini Nurmaita Aini; Selvi Nabila; Fitria Mushollini (Lembaga Pengembangan Kinerja Dosen, 2025)
According to data from the Indonesian Health Survey in 2023, the prevalence of nutritional status in the elderly in Indonesia showed that 19.3% of the elderly were obese, while 8.6% were malnourished. This research method was conducted with a descriptive approach to see the description of anthropometric nutritional status according body mass index (BMI) in the community in Limau Manis Subdistrict, Padang. Anthropometric data was collected through measurements of height and weight, while demographic data included information on age and gender. This study aims to analyze anthropometric patterns in 32 elderly respondents in Limau Manis Subdistrict, Padang City. The results of the analysis showed that the average BMI of the population was 65.62%, with a prevalence of overweight of 9.37%, obesity of 18.75%, and thinnes (less) 6.25%. This study concludes that the nutritional status of the elderly in Limau Manis Subdistrict, Padang City, shows variations in the distribution pattern of Body Mass Index (BMI). This finding indicates that the problem of obesity and overweight is more dominant than malnutrition in the elderly. Demographic features such as age and gender, which provide important insights for designing health intervention programs to improve the quality of life of the elderly in Limau Manis District.